The Role of HR Analytics, Entrepreneurial Orientation and Green Innovation in enhancing Organization Performance: Evidence from PLSSEM Framework - Muhammad Asif Qureshi, Muhammad Shujaat Mabarik, Shafiq UR Rehman Massan, Samiullah Sohu, Mehran Khan Tunio (International Journal of Advanced Science and Technology, 2020)
The present world has observed numerous adverse effects of worsening environmental conditions that are harmful to businesses, natural habitat, and future human survival. Following this statement, the current study aims to identify the relationship between green innovation, HR analytics, entrepreneurial orientation, and organizational performance. In particular, the present study seeks to explore the potentials of evidence-based analytics of people and business operations in driving organizational performance along with the relevant contribution of green product innovation, green process innovation, and entrepreneurial orientation. The results of PLS-SEM confirm that green innovation, HR analytics,and organizational performance have positively and significantlyinfluenced by entrepreneurial orientation. The results of partial least square equation modelling displaying likewise demonstrate that HR analytics have a positive and significant impact on organizational performance. Moreover, the results further indicate that green innovationalso hasa positive and significantimpact on organizational performance in different multinational firms in Malaysia.In simple, the results of partial least square modellingconfirm that all three components, i.e., organizational performance, green innovation, and HR analytics are significantly influenced by entrepreneurial orientation.Moreover, the results suggested that HR analytics and green innovation area significant contributor to enhancing the performance of multinational firms in Malaysia.